Learning of a non-native vowel through instructed production training - Antti Saloranta; Henna Tamminen; Paavo Alku; Maija S. Peltola (United Kingdom, 2022)
Models of second language acquisition predict that adults are unlikely to learn to produce a non-native vowel very quickly due to their reduced sensitivity to acoustic features not phonological in their native language. Earlier studies show that attention focusing training and articulatory instructions can facilitate learning of non-native speech sounds. We used an instructed listen-and-repeat paradigm with young Finnish adults to help them learn a non-native vowel in two days of training. The results indicated that adults learned to produce the vowel after just one session of training, likely as a result of the combination of explicit instructions and training that made them maximally responsive to the new acoustic features.
18th International Congress of Phonetic Sciences